Surgical extraction of a supernumerary tooth in a patient with Angelman syndrome - case report - Lipczyńska-Lewandowska, Małgorzata; Chybicki, Damian; Torbicka, Gaja; Ceranka, Michał; Janas-Naze, Anna (Journal of Education, Health and Sport, 2020)
The article discusses the problem of dental-occlusal disorders in patients with rare Angelman syndrome, based on the case report of an 8-year-old patient.